ICTs tools as didactic resources to enhance speaking skills in senior students at “Abelardo Moncayo” High School in 2021-2022 academic year - Morales Ramírez, Luis Ulises (2023)
Determine how ICTs tools as a didactic resource influence the development of speaking skills in senior students of the “Abelardo Moncayo” High School in 2021-2022 academic year.